A globally competent teacher as a citizen: a study of primary school teachers’ competences related to global citizenship - Sarıoğlu, Birgül. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2013., 2013)
Since, in the more complex world of the future, people will be more interdependent upon and interconnected with each other, the education of individuals with the competency of a global citizen is important for a more just and egalitarian world and the ability to learn to live and work together. It is a fact that teachers play a significant role and have a great responsibility within this process. This study, therefore, has been implemented with the participation of primary school teachers, who will equip the citizens of future with the competencies of global citizenship, for two main objectives. Within the compass of the first objective, the seven participants were asked to define a globally competent teacher as a citizen by means of the Normative Delphi Technique. After three rounds of application, a consensus was obtained among the participants, which constituted the definition of a globally competent teacher as a citizen. Within the domain of the second objective, the global competency areas regarding the knowledge, understanding, skills, values and attitudes that the six participants have as globally competent teachers were analysed in several stages by means of Interpretative Phenomenological Analysis. As a result of the analysis conducted and based on the prepared scale, twenty five of the fifty one emergent themes listed under the eight super-ordinate themes which are regarded as the sub-competency areas of global citizenship competency were observed in the participants. The analysis of how do teachers’ competences diverge and converge in terms of having competence in the super-ordinate themes has been conducted in two stages and in accordance with the observed emergent themes. In this sense, it has been accepted that the participants converge on the existence of super-ordinate themes of “diversity, value and respect” and “empathy and sense of common humanity” and the absence of the super-ordinate themes of “critical thinking”, “ability to argue effectively” and “commitment to social justice and equity”. It has been accepted that they diverge on the super-ordinate themes of “social justice and equity”, “peace and conflict” and “respect for people and things”. In the last stage of this study, a quadruple Likert evaluation was made in accordance with the total number of the observed individual emergent themes. In terms of being “a globally competent teacher as a citizen”, it has been found that, out of the six participants, one of them is “fully competent”, two of them are “competent”, two of them are “slightly competent” and one of them is “not competent”.
Keywords: Education, Elementary.; Teachers -- Education (Continuing education)